(untitled) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2022)
The choice of communication behaviour is closely related to the thoughts, values and beliefs in a society. The objective of this study is to elaborate on the refusal strategies in invitation used by native speakers of Malay (MNSs) and Japanese (JNSs) towards two different situations, namely "shopping" and "holding a party". The data collection method utilised in this study was open role-play through a social networking service by involving 20 informants in each group. The study made comparisons of the frequency of semantic formula usage in both native and intercultural contexts. The results showed that the MNSs focused more on "positive politeness", while the JNSs prioritised "negative politeness" for both situations in native contexts when the "refusal intention" was presented. Meanwhile, for the refusal to "hold a party" in native contexts, the MNSs showed indirect "interest" by frequently using "positive interjection", while the JNSs showed more explicit "interest" by frequently stating positive opinion and disappointment. Regarding the intercultural contexts, the MNSs altered their approach to enhance "negative politeness" and show more direct "interest" in response to the target language norms. This study has highlighted the influence of the "situation" and the power of openness among the MNSs who avoid conflict.